A Study Of Imaging Findings On Hrct Thorax In Corona Virus Disease 2019 (Covid-19) (Indian Journal of Applied-Basic Medical Sciences, 2022)
In December 2019, a large outbreak of a novel coronavirus infection occurred in wuhan  hubei province, china. The disease caused by the virus, named novel coronavirus disease  (COVID-19) by the world health organization (WHO) can be spread through human to  human contact. In human coronavirus can cause spectrum of diseases ranging from  asymptomatic patient, simple cold cough to severe acute respiratory syndrome ( SARS).  HRCT is very useful to see the extent of disease spread in lungs and to assess the severity  of infection. It also helps in monitoring the response and therapeutic effectiveness and  prognosis. AIMS AND OBJECTIVES: 1]To evaluate the various HRCT thorax Findings in RT PCR confirmed patients of covid-19 infection. 2] To correlate the findings of HRCT of  thorax with patient’s clinical symptoms.
Keywords: COVID-19; WHO; AIMS AND OBJECTIVES; HRCT; RT PCR